A Pilot Study of Heart Rate Variability Biofeedback Therapy in the Treatment of Perinatal Depression on a Specialized Perinatal Psychiatry Inpatient Unit - Beckham, Jenna (2012)
PURPOSE: Heart rate variability biofeedback (HRVB) therapy may be useful in treating the prominent anxiety features of perinatal depression. We investigated the use of this non-pharmacologic therapy among women hospitalized with severe perinatal depression. METHODS: Three questionnaires, the State Trait Anxiety Inventory (STAI), Warwick Edinburgh Mental Well-Being Scale (WEMWBS), and Linear Analog Self Assessment (LASA), were administered to fifteen women in a specialized inpatient perinatal psychiatry unit. Participants were also contacted by telephone after discharge to assess continued use of HRVB techniques. RESULTS: The use of HRVB was associated with an improvement in all three scales. The greatest improvement (−13.867, p<0.001 and −11.533, p<0.001) was among STAI scores. A majority (81.9%, n=9) of women surveyed by telephone also reported continued frequent use at least once per week, and over half (54.6%, n=6) described the use of HRVB techniques as very or extremely beneficial. CONCLUSIONS: The use of HRVB was associated with statistically significant improvement on all instrument scores, the greatest of which was STAI scores, and most women reported frequent continued use of HRVB techniques after discharge. These results suggest that HRVB may be particularly beneficial in the treatment of the prominent anxiety features of perinatal depression, both in inpatient and outpatient settings.